Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1051/rnd:19990207
|View full text |Cite
|
Sign up to set email alerts
|

Caecal microflora and fermentation pattern in exclusively milk-fed young rabbits

Abstract: -Thirty-two SPF New Zealand White rabbits of both sexes were used in this experiment. They were sequentially slaughtered at 22, 29, 35 and 42 days of age. The rabbits were only milked by their mother and by foster mothers (no access to solid food) throughout the experiment. They exhibited a caecal fermentation pattern that turned towards a proteolytic metabolic activity (high levels in NH 3 and in branched-chain fatty acids and valeric acid: 17 mmol ' L ' ' and 1 mmol-L-', on average, respectively). The absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 13 publications
(12 reference statements)
2
22
0
1
Order By: Relevance
“…The findings of this study concerning the caecal VFA content show a tendency similar to that of the experimental results obtained by Padilha et al (1996) with rabbits suckled twice daily up to the age of 42 days, reared exclusively on milk. The total caecal VFA concentration measured by the above-mentioned authors (12.5 mmol/L) was substantially higher than that found in our study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The findings of this study concerning the caecal VFA content show a tendency similar to that of the experimental results obtained by Padilha et al (1996) with rabbits suckled twice daily up to the age of 42 days, reared exclusively on milk. The total caecal VFA concentration measured by the above-mentioned authors (12.5 mmol/L) was substantially higher than that found in our study.…”
Section: Discussionsupporting
confidence: 88%
“…This may provide an explanation for the mass colonisation at an early stage by Bacteroides also observed in the rabbits suckled twice daily (see below). In the same experiment performed by Padilha et al (1996) the concentration of branched-chain volatile fatty acids and valeric acid remained at high levels throughout the experimental period. In the present study high concentrations were recorded prior to weaning in the rabbits suckled twice daily, which indicates that more intensive proteolytic fermentation processes were taking place.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Presumably the initially higher coliform count found in Group FF was also due to free nursing and more faecal pellets left behind the doe. Previous studies [7,15,16] showed that twice-a-day nursing resulted in higher coliform counts in addition to the higher lactobacillus counts. The higher coliform counts found in Group CN between days 6 and 10 were probably attributable to the slower development of the bacteroides and lactobacillus flora.…”
Section: Discussionmentioning
confidence: 97%
“…Padilha et al (1996), estudando a microflora cecal e o padrão de fermen- Blas et al (1994), segundo os quais dietas com alto teor de amido são uma das possíveis causas de problemas digestivos antes e após a desmama. Maertens (1992) também mencionou que, para evitar problemas digestivos, níveis superiores a 15% de amido na dieta não são recomendáveis para coelhos jovens.…”
Section: Resultsunclassified